Death and severe morbidity in isolated periviable small‐for‐gestational‐age fetuses. (1st June 2022) - Meler, Eva; Mazarico, Edurne; Peguero, Anna; Gonzalez, Alba; Martinez, Judit; Boada, David; Vellvé, Killian; Arca, Gemma; Gómez‐Roig, Maria Dolores; Gratacós, Eduard; Figueras, Francesc
Abstract: Objective: This study aims to predict perinatal death or severe sequelae in isolated small‐for‐gestational‐age fetuses, diagnosed at a periviable gestational age, based on ultrasound and Doppler parameters at diagnosis. Design: Observational study. Setting: A tertiary perinatal centre. Population: A cohort of singleton non‐malformed fetuses suspected to be small for gestational age (estimated fetal weight, EFW, <10th centile) diagnosed at 22.0–25.6 weeks of gestation. The following parameters were recorded at diagnosis: severe smallness (<3rd centile); absent or reversed end‐diastolic velocity in umbilical artery; abnormal middle cerebral artery Doppler; abnormal cerebroplacental ratio; abnormal uterine artery Doppler; and absent or reversed end‐diastolic velocity in the ductus venosus. Methods: Logistic regression analysis. Main outcome measures: Predictive performance of EFW and Doppler parameters for short‐term adverse outcome of perinatal morbimortality and composite serious adverse outcomes (death, neurological impairment or severe bronchopulmonary dysplasia). Results: A total of 155 pregnancies were included. There were 13 (8.4%) intrauterine and 11 (7.7%) neonatal deaths. A short‐term adverse perinatal outcome occurred in 40 (25.8%) pregnancies. There were 31 (20%) cases of serious adverse outcomes. For the prediction of serious adverse outcomes, the combination of absent or reversed end‐diastolic velocity in the umbilical artery and impaired middle cerebral artery detected by Doppler evaluation achieved a detection rate of 87%, with a false‐positive rate of 14% (accuracy 86%). Conclusion: In periviable isolated small‐for‐gestational‐age fetuses, a Doppler evaluation of the umbilical and fetal brain circulation can accurately predict short‐term adverse perinatal complications and serious adverse outcomes. Abstract : This article includes Author Insights, a video abstract available at: https://vimeo.com/bjogabstracts/authorinsights17181